MATHEMATICAL SIMULATION OF WELDING DISTORTIONS IN THIN PLATES - Afshin Kheidari Monfared; A. F. Panteleenko (Наука и техника)
Welding is a crucial manufacturing process and widely used for manufacturing various products including ships, automobiles, trains and bridges. Welding distortions often occur in welded structures of thin plates due to relatively low stiffness and result in their warpage during assembly process and high manufacturing cost. Therefore, prediction and reduction of welding distortions are important in order to improve quality of welded structures. Welding distortion during the assembly process is caused not only by local shrinkage due to rapid heating and cooling. 3-D thermo-elastic-plastic finite element method (FEM) has been used to simulate single-bead-on-plate welding with 1 mm thickness. Experiments have been carried out to prove the simulated results. Comparison of the experimental results and FEM simulation results has confirmed that the proposed method efficiently  predicts level of  welding distortions while making single-bead-on-plate welding with 1 mm thickness.